High-sensitivity measurement of diverse vascular plant-derived biomarkers in high-altitude ice cores - Makou, Matthew C.; Thompson, Lonnie G.; Montluçon, Daniel B.; Eglinton, Timothy I. (GEOPHYSICAL RESEARCH LETTERS, 2009)
Semi-volatile organic compounds derived from burned and fresh vascular plant sources and preserved in high-altitude ice fields were detected and identified through use of recently developed analytical tools. Specifically, stir bar sorptive extraction and thermal desorption coupled with gas chromatography/time-of-flight mass spectrometry allowed measurement of multiple biomarkers in small sample volumes (<= 30 ml). Among other compounds of interest, several diterpenoids, which suggest inputs from conifers and conifer burning, were identified in post-industrial era and older Holocene ice from the Sajama site in the Bolivian Andes, but not in a glacial period sample, consistent with aridity changes. Differences in biomarker assemblages between sites support the use of these compounds as regionally constrained recorders of vegetation and climate change. This study represents the first application of these analytical techniques to ice core research and the first indication that records of vegetation fires may be reconstructed from diterpenoids in ice. Citation: Makou, M. C., L. G. Thompson, D. B. Montlucon, and T. I. Eglinton (2009), High-sensitivity measurement of diverse vascular plant-derived biomarkers in high-altitude ice cores, Geophys. Res. Lett., 36, L13501, doi: 10.1029/2009GL037643.